Higher level of heme oxygenase-1 in patients with stroke than TIA - Li, Xin; Song, Guangfu; Jin, Yuling; Liu, Hongwei; Li, Changqing; Han, Chengwu; Ren, Shiyan (Journal of Thoracic Disease; Vol 6, No 6 (June 26, 2014): Journal of Thoracic Disease, 2014)
Background: There is a reverse relationship between serum bilirubin level and incidence of stroke, heme oxygenase-1 (HO-1) can catalyze heme into bilirubin, it is unknown the association of HO-1 level with risk of stroke. Methods: Sixty patients with stroke and fifty patients with transient ischemic attack (TIA) were recruited. Serum level of HO-1, total and direct bilirubin, alanine transaminase, live function, lipid profile and infection status of patients were measured. Results: Significant differences were found between two groups in terms of serum levels of HO-1 (163.6±58.7 vs. 141.2±49.7, P=0.032), total bilirubin (10.1±4.6 vs. 15.8±2.7, P